COMPETITIVE POTENTIAL AS A KEY TO BUSINESS DEVELOPMENT (Development Service Industry Management, 2024)
The article examines the concept of a company's potential and its competitive potential as key elements of strategic management. It explores the evolution of the term "potential" from classical resource theories of the 18th–19th centuries to modern multidimensional approaches, which integrate material, human, financial, innovative, and intellectual resources. Particular attention is paid to defining competitive potential, viewed as a combination of internal and external resources and capabilities that can provide a company with long-term competitive advantage.The scientific analysis covers the main approaches to defining the concepts of "potential" and "competitive potential," including resource-competency, systemic, dialectical, and strategic approaches. The article proposes its own interpretation of these terms, emphasizing their multidimensional and dynamic nature. Potential is understood as the combination of a company's resources, opportunities, abilities, and competencies that can be mobilized, as well as the efficiency of their use to achieve strategic and operational goals. Competitive potential is defined as the combination of internal and external resources, opportunities, competencies, and abilities that a company can leverage to achieve competitive advantages in the market.The article also highlights the factors influencing the management of competitive potential, including economic changes, political instability, technological innovations, and changes in demand. Particular attention is paid to analyzing external and internal factors that affect the competitiveness of companies in a dynamic market environment. The article emphasizes the necessity of adaptation and innovative development to ensure long-term competitive advantage.
Keywords: potential; competitive potential; adaptation; development; competitiveness